Textbook Provision for All in Ethiopia : Lessons Learned from the General Education Quality Improvement Project - Woldetsadik, Girma; Raysarkar, Chandrani (World Bank, Washington, DC, 2017)
While Ethiopia has experienced remarkable improvement in access to education, quality of education has hardly kept pace. An acute shortage of teaching/learning materials has particularly hampered learning in primary and secondary education, and the limited materials available frequently turn out to be of poor quality. For a low-income country such as Ethiopia, where class sizes are large, teachers often are untrained, and instructional time is cut short by various contingencies, access to good quality teaching/learning materials can greatly improve the quality of education. In 2010-11, to the benefit of the overall quality of education, newly developed textbooks and teaching guides started to become widely available in Ethiopia under the General Education Quality Improvement Project (GEQIP). GEQIP is a two-phase program led by the government with active participation of eight development partners; and all funding sources are pooled, and the World Bank is the supervising entity. The program is designed to improve quality of general education in Ethiopia through five components: curriculum reform and textbook provision; a teacher development program; a school improvement program; management and capacity building; and the use of information and communication technology in education. This report draws on a review of project documents, policy papers, and survey reports, in addition to discussions with stakeholders, to gain insight into the most common barriers to making teaching/learning materials available on a long-term basis and identify strategies for overcoming them.